ANALYSIS OF SERVICES IN THE PROCUREMENT OF GOODS AND SERVICES, ELECTRONIC PROCUREMENT SERVICES (LPSE) AT THE REGIONAL SECRETARIAT OF KARIMUN - Yuslinda, Yuslinda; Indrayani, Indrayani; Khaddafi, Muammar; Satriawan, Bambang (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
This study aims to describe and analyze transparency services and factors that affect transparency in theProcurement of Goods and ElectronicServices (LPSE) in the Sub Division ofService Management Electronic Procurement, Karimun Regency Secretariat. This research uses a qualitative approach. The results of the analysis show that the aspect of transparency indicators in general has shown that LPSE services are quite transparent. Meanwhile, based on the factors that influence it, namely thefactor communicationbetween the committee and the company, there is miscommunication and misunderstanding, technological factors where the internet is not stable, human resource factors shown by the lack of character or mental attitude of LPSE service providers,structure LPSE bureaucraticwhich is still concurrent. position with staff at the Office of Communication and Information in Maros Regency, the acceptance factor of the business community towards the transparency policy is still ineffective and inefficient in the process of procuring goods and services, as well as the factor of LPSE users who are still not maximal in using thesystem e-procurement